Electroconvulsive therapy enhances the anti-ageing hormone Klotho in the cerebrospinal fluid of geriatric patients with major depression - Hoyer, Carolin; Sartorius, Alexander; Aksay, Suna Su; Bumb, Jan Malte; Janke, Christoph; Thiel, Manfred; Kranaster, Laura (European neuropsychopharmacology, 2018)
Klotho is a humoral factor with pleiotropic effects. Most notably, Klotho deficiency is associated with a phenotype comprising organ manifestations accompanying aging including atherosclerosis and cognitive impairment. Research on the role of Klotho in affective disorder is scarce, which is surprising in light of the fact that depression is associated with accelerated cellular aging as well as aging-related phenotypes and comorbidity observed in Klotho deficiency. On these grounds we investigated Klotho levels in the cerebrospinal fluid (CSF) and serum of eight geriatric patients undergoing electroconvulsive therapy (ECT) for severe depression. We hypothesize that ECT as a highly effective antidepressant treatment leads enhances Klotho levels. We found a significant difference between pre- and post-ECT CSF Klotho (792.5pg/ml vs. 991.3pg/ml, p=0.0020), but no difference in serum Klotho (602.5 vs. 594.3, p=0.32). Moreover, CSF Klotho increase positively correlated with the number of single ECT sessions that were performed in each patient (F1, 6)=7.84, p=0.031). Conjointly, the results of our exploratory study with a small sample size suggest a central nervous system-specific impact of ECT on Klotho, which may in turn partake in mediating the antidepressant effect of ECT. We suggest the modulation of neuroinflammatory processes, which have been ascribed pathophysiological relevance within the conceptual framework of the neuroinflammation hypothesis of depression, through ECT as a potential mechanism by which Klotho is enhanced in response to treatment. Further preclinical and clinical investigation should aim for a precise identification of the role of Klotho in depressive disorder.
Available online 20 December 2017
Gesehen am 12.09.2018